KMT2D promotes proliferation of gastric cancer cells: evidence from ctDNA sequencing. Issue 4 (1st April 2021) - Li, Qiaolian; Wu, Riping; Wu, Fan; Chen, Qiang
Abstract: Background: ctDNA sequencing could be used for early cancer screening, prognosis prediction, and medication guidance. However, data of its application in gastric cancer are still lacking. In this study, using ctDNA sequencing, we aimed to screen the mutant genes closely associated with gastric cancer and to explore the impact of these genes on gastric cancer development. Methods: ctDNA for high‐throughput sequencing was obtained from gastric cancer patients, and the high‐frequency mutant gene KMT2D was identified. Immunohistochemical examination was conducted to assess the expression of KMT2D in gastric cancer tissues. KMT2D knockdown was performed to establish the stably transfected gastric cancer cells. Then, CCK8, plate clone formation assay, and Transwell assay were conducted, and a subcutaneous tumor‐bearing model was induced in nude mice to investigate the changes in cell proliferation and invasion capability. Transcriptome sequencing was also performed to investigate the differences in cellular gene expression. Results: Detection of ctDNA found 113 gastric cancer‐related mutations, 11 of which are the top 20 high‐frequency mutations of gastric cancer recorded by COSMIC (Catalogue of Somatic Mutations in Cancer, COSMIC). They are TP53, ARID1A, CDH1, PIK3CA, KMT2C, KMT2D, APC, SPEN, CTNNB1, SETBP1, and KMT2A. The gene closely related to the clinical characteristics of the patient is KMT2D. The high‐frequency mutant gene KMT2D was identified in gastric cancer tissues. The positive rate of KMT2D expression in cancer tissues was 74.3%, which was higher than that in para‐carcinoma tissues (56.8%). The knockdown of KMT2D inhibited the proliferation, invasion, and tumor formation capacity of the gastric cancer cells, causing differences in the gene expression profiles, and the expression of different functional gene clusters was up‐ or downregulated. Conclusion: The findings of this study revealed that KMT2D could be an oncogene capable of promoting gastric cancer proliferation. Abstract : The knockdown of KMT2D inhibited the proliferation, invasion, and tumor formation capacity of the gastric cancer cells, causing differences in the gene expression profiles, and the expression of different functional gene clusters was up‐ or downregulated. This revealed that KMT2D could be an oncogene capable of promoting gastric cancer proliferation.